Towards the use of Semi-structured Annotators for Automated Essay Grading - Lam, Hon; Dillon, Tharam S.; Chang, Elizabeth (IEEE, 2010)
The amount of time teachers spend grading essays has increased over the past decade, prompting the development of systems that are able to lighten the workload. Many systems have thus far used linear regression or semisupervised methods towards this objective. This paper discusses some of the main Automated Essay Grading systems, highlighting some of their strengths and weaknesses, in addition to providing a brief overview of Text Mining and meta-data annotation techniques that could be used to facilitate the process of grading essays through an automated system.